The level of motor coordination is associated with sports club participation in late childhood - Mononen Kaisu; Blomqvist Minna; Konttinen Niilo (Biomedical Human Kinetics, 2025)
Study aim: This study examined the associations between gender, the nature of sports club participation, training volume, and motor coordination in late childhood.